The analgesic effects of L-arginine and its antagonist LNAM - Al-Tahan, Farid J.; Al-Bayati, Muhannad A. A.; Askar, Salma J. (The Iraqi Journal of Veterinary Medicine, 2012)
L-arginine-Nitric oxide pathway plays an important role in a series of neurobiological functions underlying behaviors including analgesic effect and has shown a role in pain feeling which is a mediator with modulation effect in dorsal root of ganglionic neurons of spinal cord. The goal of the present study is to clarify theinfluence of L-arginine-mediated nitric oxide (NO) on pain arbitration in both sexes of mice. The reactive time to thermal stimulus, latency period, tail withdrawal and the number of foot licking and flinching in hot plate test, tail flick and formalin tests were recorded. The results showed that L-NAME (nitric oxide synthase inhibitor) has had an antinociceptive activity demonstrated as prolonged reactive time to thermal stimulus, latency period for tail withdrawal and decreasing the number of foot licking and flinching in hot plate, tail flick and formalin tests. These findings might be attributed to that intensity of pain feeling is intercede due to interference of sex hormones in both sexes of mice. In addition, from the results of L-NAME on pain sensation, it may be concluded that L-arginine-nitric oxide pathway is extravital in male in comparison with female in pain sensation.